The Challenge of Integrating Social Justice Content Into Social Work Education: Making the Abstract More Concrete. (2nd January 2020) - Funge, Simon P.; Crutchfield, Rashida M.; Jennings, Lisa K.
ABSTRACT: A national survey of social work educators teaching in CSWE-accredited social work education programs in the United States was conducted to explore their perceptions about integrating social justice content into their teaching. A content analysis of written commentary provided by 139 educators revealed four key areas relevant to their efforts: (a) the effect of program mission and integration, (b) the effect of faculty preparation and engagement, (c) the effect of students' positionality, and (d) the challenge of connecting an abstract concept to concrete practices. Findings from this study have highlighted not only the difficulties educators face trying to make this abstract concept more concrete for students but also the significance of the educational context as relevant to the challenges of meeting this obligation. Practical implications for social work education programs and educators as well as areas of further research are provided.